2007
DOI: 10.1073/pnas.0706645104
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study for Crohn's disease in the Quebec Founder Population identifies multiple validated disease loci

Abstract: Genome-wide association (GWA) studies offer a powerful unbiased method for the identification of multiple susceptibility genes for complex diseases. Here we report the results of a GWA study for Crohn's disease (CD) using family trios from the Quebec Founder Population (QFP). Haplotype-based association analyses identified multiple regions associated with the disease that met the criteria for genome-wide significance, with many containing a gene whose function appears relevant to CD. A proportion of these were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
119
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(122 citation statements)
references
References 35 publications
2
119
0
1
Order By: Relevance
“…14 Subsequently, more studies have also associated this R/Q single nucleotide polymorphism with other diseases from different populations. 9,10,15,[17][18][19] Although investigating the IL23R for novel polymorphic elements, we discovered a range of novel splice variants of IL23R transcripts, greatly extending an earlier study by Zhang et al 20 from early 2006. We believe that understanding the role of these variants and how their presence is controlled will give us novel insight to the role of IL-23 in human Crohn's disease.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…14 Subsequently, more studies have also associated this R/Q single nucleotide polymorphism with other diseases from different populations. 9,10,15,[17][18][19] Although investigating the IL23R for novel polymorphic elements, we discovered a range of novel splice variants of IL23R transcripts, greatly extending an earlier study by Zhang et al 20 from early 2006. We believe that understanding the role of these variants and how their presence is controlled will give us novel insight to the role of IL-23 in human Crohn's disease.…”
Section: Introductionsupporting
confidence: 59%
“…6,7 The importance of IL-23R in controlling innate immunity through Th17 cells may underscore why the IL23R gene also has been demonstrated to confer susceptibility to several autoimmune diseases, including psoriasis, 8,9 ankylosing spondylitis, 10 multiple sclerosis [11][12][13] and inflammatory bowel diseases (both Crohn's disease and/or ulcerative colitis). 14,15 In addition, a separate study by the Wellcome Trust Case Control Consortium and the Australo-Anglo-American Spondylitis Consortium found evidence to suggest that IL23R may be a common susceptibility factor for the major 'seronegative' diseases. 16 A recent genome-wide association (GWA) study first demonstrated that IL23R is one of the genetic factors contributing to Crohn's disease.…”
Section: Introductionmentioning
confidence: 99%
“…Detailed genetic characterization VE Garcia et al diseases including IBD (particularly adult and pediatric Crohn's disease), [16][17][18][19][20][21][22][23][24] AS, 25,26 and GO. 27 It is possible that IL23R variants also underlie susceptibility to celiac disease, 28 Graves' disease without ophthalmopathy 27 and multiple sclerosis, 28,29 although the evidence is not currently strong for celiac disease and Graves' disease without opthalmopathy and is contradictory for multiple sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…11 These results have been verified in four independent studies [12][13][14][15] and have paralleled association studies in related diseases. One of the IL23R missense SNPs implicated in psoriasis, R381Q, has also been strongly associated with several autoinflammatory phenotypes: several studies have found R381Q-mediated predisposition to adult inflammatory bowel disease (IBD), especially Crohn's disease [16][17][18][19][20][21] and pediatric Crohn's disease in individuals of European descent, [22][23][24] two sizable studies reported association of multiple IL23R SNPs with ankylosing spondylitis (AS) 25,26 and a North American study demonstrated IL23R susceptibility for Graves' ophthalmopathy (GO). 27 IL23R polymorphisms have also been studied in celiac disease with mildly significant results 28 and multiple sclerosis with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Testing of this SNP in our own screening and replication cohorts identifies an association signal that is equivalent in strength and that is highly correlated to rs9858213, with combined results providing overwhelming evidence that this region contains a gene for IBD (p value < 10 −12 ). A second recent GWA association study (47), also reports a significant association signal within the same region for marker rs11718165, an intronic SNP also located in BSN. The authors report several associated SNPs across a 1.2 Mb region but do not narrow down the association further.…”
Section: Discussionmentioning
confidence: 99%